Opioid Control of Renal Excretion of Water and Sodium - (:unkn) unknown (My University, 2003)
The kidneys act to regulate total body water and sodium via numerous neural and humoral mechanisms, including pathways that involve the renal sympathetic nerves, antidiuretic hormone, atrial natriuretic factor, and the renin-angiotensin-aldosterone system. In addition to these pathways, evidence indicates that opioid peptide systems participate in regulation of the renal excretory function by modulating neural and/or humoral pathways within the kidneys, periphery or central nervous system. Briefly, this premise stems from the following findings: a) central, peripheral, and intrarenal administration of native and synthetic opioid agonists produces changes in the renal excretion of water and sodium, b) endogenous central opioid mechanisms participate in the cardiovascular and renal responses produced by psychoemotional (air jet stress) and dietary (sodium deficiency) stress, and c) endogenous opioid systems contribute to the deranged renal excretory responses observed in the pathology of cirrhosis with ascites. The actions of opioids are mediated by 3 types of opioid receptors named mu, kappa and delta. Administration of selective opioid agonists can produce diuresis/antidiuresis and natriuresis/antinatriuresis depending on the type of opioid receptors activated. To completely understand how opioid systems influence kidney function, it is important to understand how each opioid system acts individually or in concert to alter renal function. In that regard, considerable research has been performed to elucidate the role of mu, kappa, delta and the recently discovered opioid receptor-like 1 (ORL-1) receptors in renal excretory function. The purpose of this article is to provide a brief review of the particular renal responses produced by opioids and the mechanism(s) by which these compounds affect renal function.
Keywords: ADH; Diuresis; Kidney; Natriuresis; Opioids; Renal sympathetic nerves